The Shaping of Form and Structure in Informal Settlements: A Case Study of Order and Rules in Lebak Siliwangi, Bandung, Indonesia - Paul Jones (Journal of Regional and City Planning, 2019)
This paper explores the relations between order and informality by focusing on the rules by which the physical form and structure evolve and is shaped in informal settlements. Central to improved planning and management of informal settlements and the city generally is a deeper understanding of what constitutes order and the underlying rules by which the physical ordering of densely populated informal settlements takes place. This is important as the existing spatial and related patterns in informal settlements are portrayed as chaotic, dysfunctional, and unplanned, with many residents seen as a source of social problems to be 'fixed' by physical solutions. Such negative stenotypes strongly influence the nature of 'top-down' policies underpinning upgrading programs. Using a case study of kampung Lebak Siliwangi in northern Bandung, Indonesia, this paper contextualizes notions of local and 'bottom up' order by identifying the rules by which the physical order and resulting spatial patterns unfold. The notion of order as seen in Lebak Siliwangi is locally self-made, not top-down, with the layout and arrangement of the complex urban fabric defined by clear patterns of sequencing and a systematic aggregation of adaptations. In this setting, the paper identifies the contextual rules, principles and activities that shape the form and structure of settlement in Lebak Siliwangi with a focus on settlement structure, public/private interface form types, and the nature of progressive change to housing.Abstrak. Makalah ini mengeksplorasi hubungan antara keteraturan dan informalitas dengan fokus pada aturan-aturan dimana bentuk fisik dan struktur berkembang dan dibentuk dalam permukiman informal. Hal yang penting dalam perencanaan dan pengelolaan permukiman informal dan kota pada umumnya adalah pemahaman yang lebih dalam tentang apa yang merupakan keteraturan dan aturan yang mendasari dimana keteraturan fisik dari permukiman informal yang padat terjadi. Ini penting karena pola spasial dan terkait yang ada di permukiman informal digambarkan sebagai kacau, disfungsional, dan tidak terencana, dengan banyak penduduk dipandang sebagai sumber masalah sosial yang harus 'diperbaiki' dengan solusi fisik. Stenotip negatif semacam itu sangat memengaruhi sifat kebijakan 'top-down' yang mendukung program peningkatan. Dengan menggunakan studi kasus pada kampung Lebak Siliwangi di Bandung bagian utara, Indonesia, makalah ini mengontekstualisasi gagasan tatanan lokal dan 'bottom up' dengan mengidentifikasi aturan-aturan yang dengannya tatanan fisik dan pola spasial yang dihasilkan berkembang. Gagasan keteraturan seperti yang terlihat di Lebak Siliwangi adalah buatan lokal, bukan top-down, dengan tata letak dan pengaturan struktur perkotaan yang rumit yang ditentukan oleh pola pengurutan yang jelas dan agregasi adaptasi yang sistematis. Dalam situasi ini, makalah ini mengidentifikasi aturan kontekstual, prinsip dan kegiatan yang membentuk bentuk dan struktur pemukiman di Lebak Siliwangi dengan fokus pada struktur pemukiman, jenis bentuk antarmuka publik/pribadi, dan sifat perubahan progresif ke perumahan.Kata Kunci.  keteraturan, aturan, evolusi, bentuk, struktur, informalitas, permukiman informal.